2016
DOI: 10.1016/j.str.2016.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Dual-Mode Wnt Regulator Kremen1 and Insight into Ternary Complex Formation with LRP6 and Dickkopf

Abstract: SummaryKremen 1 and 2 have been identified as co-receptors for Dickkopf (Dkk) proteins, hallmark secreted antagonists of canonical Wnt signaling. We present here three crystal structures of the ectodomain of human Kremen1 (KRM1ECD) at resolutions between 1.9 and 3.2 Å. KRM1ECD emerges as a rigid molecule with tight interactions stabilizing a triangular arrangement of its Kringle, WSC, and CUB structural domains. The structures reveal an unpredicted homology of the WSC domain to hepatocyte growth factor. We fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 41 publications
2
46
0
Order By: Relevance
“…Furthermore, DKK1 binding to LRP6 can induce a conformational change that may allosterically impede Wnt binding (Matoba et al , ). DKK1 can also form a ternary complex with the kremen 1 co‐receptor and LRP6, possibly leading to depletion of LRP6 from the cell surface and decreased signalling; however, this model remains controversial (Mao et al , ; Semenov et al , ; Wang et al , ; Zebisch et al , ). Although DKK1 clearly regulates Wnt signalling through inhibition of the β‐catenin‐dependent pathway, this may be an oversimplification because DKK1 has also been linked to the activation of β‐catenin‐independent Wnt signalling.…”
Section: Discovery and Characterization Of Dkk1mentioning
confidence: 99%
“…Furthermore, DKK1 binding to LRP6 can induce a conformational change that may allosterically impede Wnt binding (Matoba et al , ). DKK1 can also form a ternary complex with the kremen 1 co‐receptor and LRP6, possibly leading to depletion of LRP6 from the cell surface and decreased signalling; however, this model remains controversial (Mao et al , ; Semenov et al , ; Wang et al , ; Zebisch et al , ). Although DKK1 clearly regulates Wnt signalling through inhibition of the β‐catenin‐dependent pathway, this may be an oversimplification because DKK1 has also been linked to the activation of β‐catenin‐independent Wnt signalling.…”
Section: Discovery and Characterization Of Dkk1mentioning
confidence: 99%
“…Dkks in the Dkk1/2/4 class, in contrast, are thought to inhibit Wnt/b-catenin by binding directly to the ectodomains of LRP5/6, and thus interfering with Wnt ligand binding (Bao et al, 2012). Kremens are co-receptors for Dkks, and can also bind LRP5/6 in a ternary complex (Zebisch et al, 2016); interestingly, in the presence of Dkk, Kremen proteins enhance Wnt inhibition, while in the absence of Dkk they potentiate LRP5/6 mediated signalling, thus acting as a bi-modal switch during Wnt signalling.…”
Section: S Bertrand Et Almentioning
confidence: 99%
“…In vertebrates, two Kremens have been identified, Kremen1 and Kremen2, with clear roles in potentiating the Wnt inhibitory effects of Dkk1 (Cruciat and Niehrs, 2013) via direct binding in a ternary complex with LRP6 (Zebisch et al, 2016). In the B. floridae genome, four Kremen genes (Krm1, -2, -3, -4) with close affinity and similar domain structure content to vertebrate Kremens 1 and -2 have been localized to the same scaffold, and thus appear to have evolved via tandem duplication (Zhang and Mao, 2010).…”
Section: Co-regulatorsmentioning
confidence: 99%
“…Thirdly, in silico analyses identify it as pathogenic and an alignment of protein sequences has revealed that cysteine‐111 is evolutionarily conserved. Fourthly, p.C111 is a part of disulfide bonds, which are essential in maintaining protein integrity . The mutation is expected to cause unfavourable kringle domains, which play roles in various biological processes.…”
mentioning
confidence: 99%
“…Fourthly, p.C111 is a part of disulfide bonds, which are essential in maintaining protein integrity. 7 The mutation is expected to cause unfavourable kringle domains, which play roles in various biological processes.…”
mentioning
confidence: 99%